2019
DOI: 10.1096/fj.201900017r
|View full text |Cite
|
Sign up to set email alerts
|

Lack of galectin‐1 exacerbates chronic hepatitis, liver fibrosis, and carcinogenesis in murine hepatocellular carcinoma model

Abstract: Chronic liver inflammation (CLI) is a risk factor for development of hepatocellular carcinoma (HCC). Galectin‐1 (Gal1) is involved in the regulation of inflammation, angiogenesis, and tumorigenesis, exhibiting multiple anti‐inflammatory and protumorigenic activities. We aimed to explore its regulatory role in CLI and HCC progression using an established model of CLI‐mediated HCC development, Abcb4 [multidrug‐resistance 2 (Mdr2)]‐knockout (KO) mice, which express high levels of Gal1 in the liver. We generated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Supporting these findings, GH induced hepatic GAL1 expression when this hormone was continuously administered for a short period. Interestingly, the results obtained with murine HCC models suggested that GAL1 may act as a protective anti-inflammatory agent at early stages of chronic liver pathology and as a pro-tumorigenic agent at late stages of the disease contributing to HCC growth and metastasis (37, 38). Because of the broad immunosuppressive and pro-angiogenic activities of GAL1 within tumor microenvironments (20, 29, 39), its upregulation could, at least in part, mediate GH-driven hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these findings, GH induced hepatic GAL1 expression when this hormone was continuously administered for a short period. Interestingly, the results obtained with murine HCC models suggested that GAL1 may act as a protective anti-inflammatory agent at early stages of chronic liver pathology and as a pro-tumorigenic agent at late stages of the disease contributing to HCC growth and metastasis (37, 38). Because of the broad immunosuppressive and pro-angiogenic activities of GAL1 within tumor microenvironments (20, 29, 39), its upregulation could, at least in part, mediate GH-driven hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are some findings suggesting that galectin-1 inhibits the development of acute and chronic inflammation in some disease models associated with inflammation. [10][11][12][13]26,27 Injection of phospholipase A2 (PLA-2) with or without galectin-1 in rats inhibited PLA-2-induced paw edema by reducing leukocyte infiltration and mast cell degranulation. Also, it showed a protective effect against acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aged knockout mice displayed earlier hepatocarcinogenesis and increased tumor growth. The mechanisms underlying these effects revealed modulation of pro-oncogenic cytokines, including osteopontin, Ntrk2 (TrkB) and S100A4 as critical targets of Gal1 activity ( Potikha et al, 2019 ). Conversely, in ovary cancer models Gal1 contributes to tumor-promoting inflammation linking TLR5-dependent IL-6 production and distant tumor progression ( Rutkowski et al, 2015 ).…”
Section: Tumor-promoting Inflammationmentioning
confidence: 99%